Relationships between normalized difference vegetation index (NDVI) and other traits of tropical testcross maize (Zea mays L.) hybrids under drought and wellwatered conditions - Adebayo, M.A.; Menkir, A.; Hearne, S. (2014)
Normalized difference vegetation index (NDVI) is a non-destructive measure of green vegetation growth or above ground biomass of a crop. NDVI may also be used to evaluate traits such as early vigour and stay green which are important for adaptation to drought stress. In the present study, the relationships between NDVI and grain yield as well as other measured agronomic and drought-adaptive traits were examined under drought stress and full irrigation conditions in a trial composed of testcross hybrids of exotic and adapted maize inbred lines. A trial composed of 44 maize hybrids comprising 41 testcrosses and 3 hybrid checks were evaluated under simulated drought stress and well-watered conditions at Ikenne in the rainforest agro-ecology of Nigeria during the dry seasons of 2010 and 2011. Each trial was laid out in the field in a 4 x 11 ?-lattice design with three replications. NDVI had higher correlation coefficients with grain yield under full irrigation than under drought stress, though the relationships were generally weak. NDVI had stronger association with grain yield at 8-leaf stage than at 3-leafed stage under full irrigation conditions. The R2 values of NDVI_1 with grain yield and plant height under both irrigation treatments were ? 0.20. The R2 values of NDVI_2 with grain yield were 0.31 and 0.45 under drought and full irrigation environments, respectively, while the values with plant height under drought and full irrigation conditions were 0.48 and 0.38, respectively. Our results suggest that NDVI may be a useful secondary trait for phenotyping maize germplasm in drought tolerance maize breeding program especially under well-watered conditions.